A Multinational Green Supply Chain Model Suffered to Import Tariff. (20th June 2020) - Zhai, Mengyue; Liu, Mingwu; Fu, Hong; Fu, Qiaoling
Abstract : This paper considers a multinational green supply chain (MGSC), composed of a manufacturer and a foreign retailer affected by import tariff. The main theme of this paper is to explore supply chain decisions and coordination contract. Four decision models were investigated: (1) the centralized decision supply chain model (model CS), (2) the decentralized decision supply chain model (model DS), (3) the R&D cost sharing contract model (model RD) with the retailer sharing a portion of green R&D cost, and (4) the quantity discount-cost sharing contract model (model QD), which combined a quantity discount contract with a cost sharing contract. The equilibrium decisions of these models were derived. The R&D cost sharing contract was found to improve greenness and performance of the supply chain but cannot reach the optimal performance compared to the centralized decision model. While the quantity discount-cost sharing contract can achieve a perfect coordination of MGSC. Furthermore, import tariff has an adverse effect on the performance of MGSC. The increase in tariff shrinks the threshold of the highest wholesale price and quantity discount coefficient offered by the manufacturer, which will hamper the cooperation of supply chain. However, the enhancement of consumers' green preference is conducive to encourage the retailer to participate in cooperation and smoothen the adverse effects of tariff fluctuation. In the same model, the adverse effect of tariff on product greenness and the retail price does not change with the increase in its value. However, the adverse effect on the green performance price ratio and the profits from all parties in the supply chain are slow.